Local Wisdom as the Basis for Determination of Legislation Related to Public Order - Abdul Madjid (Faculty of Law, University of Merdeka Malang, 2023)
This paper reviews how the mechanism for absorbing local wisdom values in the formation of criminal sanctions in the process of forming regional regulations in districts, namely Ponorogo, Magetan, and Madiun Regencies, East Java Province. This research is empirical legal research using a juridical-sociological approach. Based on the results of the discussion, local wisdom in the studied districts, which is characterized by sociological studies as a Mataraman cultural character, does not exist in the formation of local regulations on public order. It can be seen that there are differences in the determination of criminal sanctions in regional regulations regarding public order. This is because there is still a need for more specific regulations governing the mechanism for forming regional regulations to accommodate the interests of local wisdom to be contained in norms as sanctions in regional regulations. Thus, in the future, it is necessary to develop national standard parameters for making regional regulations and design a linkage mechanism between these standard mechanisms and the legal values of local life that live in society, which can bridge the two domains.How to cite item: Madjid, Abdul. â€œLocal Wisdom as the Basis for Determination of Legislation Related to Public Order.â€ Jurnal Cakrawala Hukum 14 no. 2 (2023): 114-125. DOI: 10.26905/idjch.v14i2.10843.